Application and Innovation of Computer Graphics Design Courses in Journalism Education under the Context of Media Convergence - Shi, Mo (Transactions on Social Science, Education and Humanities Research, 2024)
With the deep development of media convergence, journalism education faces new challenges and opportunities. Computer graphics design plays an increasingly important role in news gathering, editing, and dissemination. This paper aims to explore the current application of computer graphics design in journalism education under the context of media convergence and proposes innovative strategies to meet the talent development needs of the multimedia era.